Hygro‐Dynamic and Conductive Actuator That Restructures and Heals by Water - Chen, Qing; Künniger, Tina; Song, Qun; Zhang, Kai; Chumakov, Andrei; Bulut, Yusuf; Harder, Constantin; Müller‐Buschbaum, Peter; Roth, Stephan V.; Braun, Artur (Advanced functional materials, 2024)
The prospects of endowing stimuli‐responsive materials with various life‐like behaviors are promoting the development of intelligent robotic and electronic devices. However, it is challenging to incorporate stimuli‐responsive actuating and healing capabilities into one single material system. Herein, the design and assembly of humidity‐responsive thin films composed of poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) and sodium carboxymethyl cellulose (NaCMC) forming a conducting polymer composite through a physically cross‐linked and hydrogen‐bonded supramolecular network are described. Owing to its enhanced dynamics of hydrogen bonding at an elevated humidity, the PEDOT:PSS/NaCMC thin film exhibits a rapid humidity‐responsive actuating performance in an environment with humidity gradient, as well as a repairing function of the structural, mechanical, electrical, and actuating properties after being damaged through a humidifying‐drying cycle. Based on a combined analytical approach, a structural model is proposed for the rearrangement of the thin film when being exposed to stepwise humidity levels at multi‐length scales. Due to the structural rearrangement powered by humidity variations, the film exhibits tunable actuating and healing performance, which makes it a promising candidate material for applications in intelligent soft robotics such as artificial muscles. A structurally rearrangeable polymer thin film is constructed and used analytical techniques to detect the structural, mechanical, electrical, and hygroscopic properties at varying humidities. Benefiting from these tunable properties, this polymer thin film shows the potential of being used as an actuator, environmental humidity sensor, and healable conductor, whose structures and functionalities can be restored by a humidifying/drying cycle.